3D in vitro Model of Vascular Medial Thickening in Pulmonary Arterial Hypertension - Morii, Chiharu; Tanaka, Hiroyoshi Y.; Izushi, Yasuhisa; Nakao, Natsumi; Yamamoto, Masaya; Matsubara, Hiromi; Kano, Mitsunobu R.; Ogawa, Aiko (Frontiers in Bioengineering and Biotechnology, 2020)
In pulmonary arterial hypertension (PAH), excessive proliferation of pulmonary artery smooth muscle cells (PASMCs) causes vascular medial thickening. Medial thickening is a histopathological hallmark of pulmonary vascular remodeling, the central disease process driving PAH progression. Pulmonary vascular remodeling causes stenosis and/or obstruction of small pulmonary arteries. This leads to increased pulmonary vascular resistance, elevated pulmonary arterial pressure, and ultimately right heart failure. To improve the survival of PAH patients, which remains at approximately 60% at 3 years after diagnosis, the development of novel PAH-targeted drugs is desired. To this end, a detailed understanding of the mechanisms underlying excessive PASMC proliferation and the medial thickening that ensues is necessary. However, a lack of in vitro models that recapitulate medial thickening impedes our deeper understanding of the pathogenetic mechanisms involved. In the present study, we applied 3-dimensional (3D) cell culture technology to develop a novel in vitro model of the pulmonary artery medial layer using human PAH patient-derived PASMCs. The addition of platelet-derived growth factor (PDGF)-BB, a mitogen known to promote excessive PASMC proliferation in PAH, resulted in increased thickness of the 3D-PAH media tissues. Conversely, administration of the PDGF receptor inhibitor imatinib or other clinical PAH drugs inhibited this medial thickening-inducing effect of PDGF-BB. Altogether, by using 3D cell culture technology, we report the generation of an in vitro model of medial thickening in PAH, which had hitherto not been successfully modeled in vitro. This model is potentially useful for assessing the ability of candidate PAH drugs to suppress medial thickening.